PROBLEMS OF PROFESSIONAL ETHICS OF A LAWYER AND LEGAL RHETORIC (Conferencea, 2023)
This article discusses the main problems that hinder the development of the professional ethics of lawyers as one of the fundamental foundations of the legal profession in the Republic of Uzbekistan. A comparative legal analysis of foreign countries in this area has been carried out. The problems of the lack of codes of professional ethics for lawyers in our country are analyzed. A proposal is made to introduce professional ethics as a separate academic discipline in law schools. In addition, the importance of the legal rhetoric of a lawyer for the effective and expedient use of his speech is indicated. The author proposes to improve the standards of teaching the ethics of a lawyer and legal rhetoric in the curricula of specialized universities.